OLED with Area Defined Multicolor Emission Within a Single Lighting Element - (:unkn) unknown (Osram Opto Semiconductors Gmbh, 2007)
Disclosed is an organic electroluminescent device, comprising: a) a substrate; b) a first electrode disposed over the substrate; c) a composite light emitting layer comprising two or more light emissive materials, disposed over the first electrode; and d) a second electrode disposed over the composite light emissive layer, the electrodes commonly and singularly addressing the composite light emissive layer.
Keywords: 313/504.000; Organic electroluminescent device; Substrate; 313/506.000; 313/503.000; Electrode; 313/505.000; 445/24.000; H01J 9/24 (20060101); H01J 1/62 (20060101)